Tycoon : a novel - Robbins, Harold, 1916-1997. (New York, NY : Simon & Schuster, 1997)
Jack Lear rises from modest Jewish background to take on the WASP world, but never quite feels he's succeeded. Making his fortune as a pioneering radio and television broadcaster and founding a landmark network isn't enough - nor the money, fame and women that go with it. He continues to hunger for what he cannot have.
Keywords: Television broadcasting -- Fiction; Businessmen -- Fiction; Success -- Fiction; Adventure stories